Analisis Konsumsi Hijau pada Kegiatan Car Free Day dalam Menciptakan Ekonomi Hijau di Alun-Alun Kota Kraksaan - Pradani, Rizki Febri Eka; Putri, Sephia Eka Amalia; Safitri, Indah Nurlaili; Wulandari, Evi Sri (Universitas Nurul Jadid, 2024)
Car Free Day is an initiative by the Indonesian government to reduce air pollution and promote environmentally friendly practices. In Kraksaan City, this program not only supports local SMEs by providing selling opportunities but also attracts significant public participation. This study aimed to assess the awareness level of Car Free Day visitors regarding green consumption and to identify barriers to adopting environmentally friendly consumer behavior. Using qualitative methods and descriptive research design, data were gathered through observation, interviews, and documentation. Results indicate that both visitors and participating SMEs lack understanding of green consumption principles. Many continue to consume and utilize non-environmentally friendly products, particularly in food packaging and transport choices. This study highlights the need for targeted education and policy measures to encourage sustainable consumption patterns during public events like Car Free Day.